Novel Cationic Lipids with Enhanced Gene Delivery and Antimicrobial Activity - Fein, David E. (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Cationic lipids facilitate plasmid delivery, and some cationic sterol-based compounds have antimicrobial activity because of their amphiphilic character. These dual functions are relevant in the context of local ongoing infection during intrapulmonary gene transfer for cystic fibrosis. The transfection activities of two cationic lipids, dexamethasone spermine (DS) and disubstituted spermine (D(2)S), were tested as individual components and mixtures in bovine aortic endothelial cells and A549 cells. The results showed a 3- to 7-fold improvement in transgene expression for mixtures of DS with 20 to 40 mol% D(2)S. D(2)S and coformulations with DS, dioleoyl phosphatidylethanolamine, and DNA exhibited potent bactericidal activity against Escherichia coli MG1655, Bacillus subtilis, and Pseudomonas aeruginosa PAO1, which was maintained in bronchoalveolar lavage fluid. Complete bacterial killing was demonstrated at ∼5 μM, including gene delivery formulations, with 2 orders of magnitude higher tolerance before eukaryotic membrane disruption (erythrocyte hemolysis). D(2)S also exhibited lipopolysaccharide (LPS) scavenging activity resulting in significant inhibition of LPS-mediated activation of human neutrophils with 85 and 65% lower interleukin-8 released at 12 and 24 h, respectively. Mixtures of DS and D(2)S can improve transfection activity over common lipofection reagents, and D(2)S has strong antimicrobial action suited for the suppression of bacterial-mediated inflammation.